HIGH ADMISSION PLASMA OSMOLALITY VALUE AS IN-HOSPITAL MAJOR ADVERSE CARDIOVASCULAR EVENTS PREDICTOR IN PATIENT WITH ACUTE MYOCARDIAL INFARCTION - Zul Bahri*, Cut Aryfa Andra, Zulfikri Mukhtar, Abdul Halim Raynaldo, Yuke Sarastri & Harris Hasan (International Journal of Research Science and Management, 2020)
Background: Elevated blood urea nitrogen (BUN), blood glucose, and alteration sodium levels are common among patients with acute myocardial infarction (AMI). These parameters to be widely investigated to assess the prognosis in AMI patients. However, the combination of these parameters (BUN, blood glucose, and sodium) calculated by a certain formula in the form of plasma osmolality has not been widely studied to assess the prognosis of patients with acute myocardial infarction. This study aims to assess plasma osmolality in predicting hospital major adverse cardiovascular events (MACEs) among AMI patients. Methods: Data were collected from 118 consecutive patients with AMI in Cardiac Centre Haji Adam Malik General Hospital Medan. We measured admission plasma osmolality [1,86 (Na+) + BUN/2,8 + Glucose/18+9]. Then we observed in hospital Major Adverse Cardiovascular Outcomes (MACEs) which consist of cardiovascular mortality, acute heart failure, malignant arrhythmia, and cardiogenic shock. Statistical analysis was performed using mean difference, logistic regression, and receiver operating curve (ROC). Result: Among 118 patients, MACEs were observed in 49 (41.5%) patients with the most common MACEs was acute heart failure (25.4%). Bivariate analysis showed a significant relationship between the plasma osmolality and in hospital MACEs (p < 0.001). The plasma osmolality AUC prediction value was 78.9%. The optimal cutoff value was 279.9 mOsm/kg (sensitivity 81.6%; specificity 75.4%). In multivariate logistic regression analysis, the plasma osmolality was the strongest predictor with an OR value of 10.542 (95% CI 2.694-41.255; p-value <0.001). Conclusions: Among AMI patients, high plasma osmolality value (≥280 mOsm/kg) is a better predictor of inhospital MACEs than its components separately(BUN, glucose level, sodium)